Android-Based Smartphone Application Create Reports Results for Packaging On Garment Company: Android-Based Smartphone Application Create Reports Results for Packaging On Garment Company - Nur Alamsyah; Muhammad Yusup Iskandar (Jurnal Mantik, 2020)
Android is a mobile operating system based on Linux open for developers to create their own applications that can be used by a variety of mobile devices, so that the operating system most widely used today. With the development of the utilization of the android operating system is not only used for communication but can be used to help an industry. In the manufacture of the ongoing reporting is often a lot of manual, so it takes a long time. To solve this problem, we need the appropriate application, which can solve this problem. The author would like to make an application for smartphones based on the Android operating system for help in making a report on the packaging PT. Sansan Brothers Tex Jaya. By utilizing an application that has the writer asked,